An MTSS Based Underground Coal Mining Simulation Model - Okolnishnikov, V. (Engineering, Technology & Applied Science Research, 2018)
In the frames of simulation system, a specialized library of simulating models of mining equipment and coal seam (MTSS) was implemented. Using the specialized simulating model library of technological mining equipment an integrated model for technological processes of underground coal mining in stoping face was developed. The main goal of simulation for coal mining technological processes in stoping face is the evaluation of productivity of a cutter-loader depending on different factors like the technical parameters of the cutter-loader, size of the longwall face, geophysical state of the coal seam.